Attitude toward aging seniors and psychological well-being - Silva, Lorenna Cláudia Carvalho (2013)
The objective of this study was to investigate attitudes and psychological well-being of the elderly in Santo Antônio de Jesus-Ba. This is a descriptive, field, quantitative, where the sample was non-probabilistic, consisting of 54 seniors. The elderly showed positive attitudes towards old age and a positive sense of psychological well-being. Attitudes can act as coping mechanisms in the face of losses of old age by increasing the psychological adjustment.